Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Sure, let's go through the process of completing the square for the equation [tex]\(x^2 + 8x - 3 = 0\)[/tex] step-by-step.
1. Start with the quadratic expression: [tex]\(x^2 + 8x - 3 = 0\)[/tex].
2. Focus on the quadratic and linear terms: [tex]\(x^2 + 8x\)[/tex]. We need to complete the square for this part.
3. Take the coefficient of the [tex]\(x\)[/tex] term (which is 8) and divide it by 2:
[tex]\[ \frac{8}{2} = 4 \][/tex]
4. Square this result:
[tex]\[ 4^2 = 16 \][/tex]
5. Now, add and subtract this square (16) inside the equation to complete the square:
[tex]\[ x^2 + 8x = (x^2 + 8x + 16) - 16 \][/tex]
6. Rewrite the quadratic part as a perfect square and incorporate the constants:
[tex]\[ (x^2 + 8x + 16) - 16 - 3 = 0 \][/tex]
Simplify the constants:
[tex]\[ (x + 4)^2 - 19 = 0 \][/tex]
Therefore, when completing the square, [tex]\(x^2 + 8x - 3 = 0\)[/tex] can be transformed into:
[tex]\[ (x + 4)^2 - 19 = 0 \][/tex]
So, the left side of the equation becomes the binomial squared:
[tex]\[ (x + 4)^2 \][/tex]
And, to fill in the blanks in the steps:
[tex]\( (x + 4)^2 = \ldots \)[/tex]
The result from completing the square is:
[tex]\[ (x + 4)^2 - 19 = 0 \][/tex]
1. Start with the quadratic expression: [tex]\(x^2 + 8x - 3 = 0\)[/tex].
2. Focus on the quadratic and linear terms: [tex]\(x^2 + 8x\)[/tex]. We need to complete the square for this part.
3. Take the coefficient of the [tex]\(x\)[/tex] term (which is 8) and divide it by 2:
[tex]\[ \frac{8}{2} = 4 \][/tex]
4. Square this result:
[tex]\[ 4^2 = 16 \][/tex]
5. Now, add and subtract this square (16) inside the equation to complete the square:
[tex]\[ x^2 + 8x = (x^2 + 8x + 16) - 16 \][/tex]
6. Rewrite the quadratic part as a perfect square and incorporate the constants:
[tex]\[ (x^2 + 8x + 16) - 16 - 3 = 0 \][/tex]
Simplify the constants:
[tex]\[ (x + 4)^2 - 19 = 0 \][/tex]
Therefore, when completing the square, [tex]\(x^2 + 8x - 3 = 0\)[/tex] can be transformed into:
[tex]\[ (x + 4)^2 - 19 = 0 \][/tex]
So, the left side of the equation becomes the binomial squared:
[tex]\[ (x + 4)^2 \][/tex]
And, to fill in the blanks in the steps:
[tex]\( (x + 4)^2 = \ldots \)[/tex]
The result from completing the square is:
[tex]\[ (x + 4)^2 - 19 = 0 \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.